Performance and energy analysis of turboprop engine for air freighter aircraft with the aid of multiple regression - Kirmizi, Mehmet; Aygun, Hakan; Turan, Onder (Pergamon-Elsevier Science Ltd, 2023)
In this study, performance and energy analyses of a turboprop engine (TPE) are determined for an air freighter aircraft. For this aim, influences of different design variables involving turbine inlet temperature (TIT) ranging 1200 K and 1400 K, pressure ratio of compressor (CPR) ranging 16 and 20 and propeller efficiency (PE) ranging from 0.7 to 0.98 are elaborately searched, which helps in observing changes of specific fuel consumption (SFC), thrust force, engine power and overall efficiency related to the turboprop engine at an altitude of 6.7 km and 0.59 Mach. Based on this analysis, relations of these parameters with the mentioned design variables are researched with multiple regression method. In the light of performance results, SFC of the TPE changes from 0.2449 kg/kW.h to 0.1844 kg/kW.h due to rising PE and diminishes from 0.2263 kg/kW.h to 0.2159 kg/kW.h owing to rising TIT. On the other hand, overall efficiency of the TPE increases from 21% to approximately 40% due to rising PE and enhances from 26.3% to 28.12% due to rising TIT whereas it decreased from 27.6% to 23.5% due to increasing the CPR. Finally, the linear modeling of both SFC and overall efficiency regarding TPE with pairs of TIT and CPR variables results in about 0.97 of coefficient of determination (R2) whereas it is improved to more than 0.99 of R2 by using quadratic modeling. Moreover, for the modeling involving PE variable, R2 is computed as 0.99 with linear equations. Therefore, quadratic modeling enables R2 to slightly increase. It is thought that this analysis could benefit in knowing how much design parameters are effective on turboprop performance indicators.
Keywords: Turboprop performance; Propeller efficiency; Gas turbine engine; Multiple regression